World University Ranking : Caltech Model for University & Industry Working Together - Anon (Universiti Malaysia Perlis (UniMAP), 2012)
Organized by Academic Management Division Deputy Vice Chancellor Office (Academic and International) Chancellery Department, 12th December 2011 at Keikhlasan Hall, 10th Floor, KWSP Building, Kangar, Perlis.